Embryological Aspects and Anatomical Variations of the Inferior Vena Cava – Its Importance in Gynecologic Oncology Surgery - Stoyan Kostov; Nadezhda Hinkova; Svetla Dineva; Angel Yordabnov (Journal of Biomedical & Clinical Research, 2022)
Surgical procedures of the retroperitoneum are often performed in gynecologic oncology surgery clinics. The most complex among them is paraaortic lymphadenectomy. It is generally performed in cases of bulky lymph nodes in ovarian carcinomas and sarcomas to achieve optimal cytoreduction. In the early stages of ovarian cancer, type II non-endometrioid endometrial cancer, and in advanced stages of cervical cancer, paraaortic lymphadenectomy is an integral part of staging. Moreover, the retroperitoneum is approached in cases of retroperitoneal gynecologic sarcomas. The largest vessels of the human body – the inferior vena cava and the abdominal aorta are localized in the retroperitoneum. Therefore, iatrogenic vessel injury during oncogynecological surgery is more likely to affect the inferior vena cava. Anatomical variations of the vein additionally increase the risk of vascular lesions. Therefore, surgeons should be aware of possible anatomical variations. The present article aimed to highlight the heterogeneity of anatomical variations of the inferior vena cava related to gynecologic oncology surgery. Embryogenesis of the vein and its variations are also discussed. Additionally, some anomalies of the ureter, associated with the embryogenesis of the inferior vena cava, are mentioned.